2004
DOI: 10.1111/j.1365-2648.2003.02970.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of herbal therapies by older, community‐dwelling women

Abstract: It is important for community health nurses to be knowledgeable about the use of herbal therapies when providing care to older women because of possible interactions with other treatments, delays in seeking care, and poor quality products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 16 publications
5
12
0
Order By: Relevance
“…Similar to previous studies regarding nephrology patients or various populations (Kleshinski et al. 2003, Gozum & Unsal 2004, Rivera et al. 2005, Kara 2009), garlic was found to be the most widespread herbal therapy modality in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to previous studies regarding nephrology patients or various populations (Kleshinski et al. 2003, Gozum & Unsal 2004, Rivera et al. 2005, Kara 2009), garlic was found to be the most widespread herbal therapy modality in our study.…”
Section: Discussionsupporting
confidence: 91%
“…The use of herbal products in CRF patients seems to be especially harmful because of reasons such as nephrotoxicity, hemodynamic changes, unpredictable effects in blood pressure, blood glucose and coagulation parameters or because of electrolyte abnormalities (Dahl 2001). Similar to previous studies regarding nephrology patients or various populations (Kleshinski et al 2003, Gozum & Unsal 2004, Rivera et al 2005, Kara 2009), garlic was found to be the most widespread herbal therapy modality in our study. Garlic is used to reduce hypertension and hypercholesterolaemia by patients (Mansoor 2001, Borrelli & Izzo 2008.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are identical with those of other studies: TCM is valued among elderly people for its effectiveness in improving physiological and musculoskeletal problems, particularly in reducing pain and promoting mobility, and can be used to manage multiple chronic diseases and treat psychological disorders to improve health and well-being (Cartwright, 2007;Cheung et al, 2007;Gozum and Unsal, 2004;Najm et al, 2003;Wong et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Interest in herbal therapies has been growing rapidly in Turkey. Commonly used herbs used in Turkey include stinging nettle (U. dioica) for the treatment of illnesses (Gözum and Unsal 2004). Herbal combinations (mainly U. dioica) are also the most frequently used remedy among adult patients with cancer (Ceylan et al, 2002).…”
Section: Discussionmentioning
confidence: 99%